Impact of climatic change on sea surface temperature variation in Subei coastal waters, East China - Wang, Ran; Yu, Fei (Chinese journal of oceanology and limnology, 2014)
Sea surface temperature (SST) variation in the Subei coastal waters, East China, which is important for the ecological environment of the Yellow Sea where Enteromorpha prolifera blooms frequently, is affected by the East Asian winter monsoon (EAWM), El Niño-Southern Oscillation (ENSO), and Pacific Decadal Oscillation (PDO). In this study, correlations between climatic events and SST anomalies (SSTA) around the Subei (North Jiangsu Province, East China) Coast from 1981–2012 are analyzed, using empirical orthogonal function (EOF) and correlation analyses. First, a key region was determined by EOF analysis to represent the Subei coastal waters. Then, coherency analyses were performed on this key region. According to the correlation analysis, the EAWM index has a positive correlation with the spring and summer SSTA of the key region. Furthermore, the Niño3.4 index is negatively correlated with the spring and summer SSTA of the key region 1 year ahead, and the PDO has significant negative coherency with spring SSTA and negative coherency with summer SSTA in the key region 1 year ahead. Overall, PDO exhibits the most significant impact on SSTA of the key region. In the key region, all these factors are correlated more significantly with SSTA in spring than in summer. This suggests that outbreaks of Enteromorpha prolifera in the Yellow Sea are affected by global climatic changes, especially the PDO.